Urban development and 2030 Agenda: challenges and solutions for sustainable cities - Silva, Marcia Regina Farias da; Dias, Nildo da Silva; Silva, Carlos Aldemir Farias da; Lima, Alexandre de Oliveira (National Journal of City Management, 2021)
Discussions about the Sustainable Development Goals (SDGs) and urban sustainability can help in the search for elucidating urban problems, considering the imprecision and conflicts that orbit around the debate on urban sustainability and the term sustainable development. This debate can contribute to future actions and proposals for urban public policies. Thus, the objective was to discuss Objective 11 of the 2030 Agenda, which deals with Sustainable Cities and Communities, from the perspective of collaborating with the debate on urban sustainability, based on the case study of Mossoró (RN). As a methodological procedure, documental and bibliographical research was carried out, around themes such as urban sustainability, sustainable development, and the 2030 Agenda, aiming to raise a theoretical reflection on these themes. Primary sources were researched in public archives of the Municipality of Mossoró and academic websites. In addition, 70 questionnaires were applied together to students and public servants of Mossoro’s public university . It was found that the city only fulfills its social function when it guarantees its inhabitants, habitation; circulation, leisure; work, accessibility, education, and health. The challenges to thinking about sustainable cities are numerous and, on the other hand, the solutions are in place, and, therefore, the admission of public policies aligned with the production and adoption of technologies for sustainable cities is the possible path.